Greening Existing Buildings in Brunei Darussalam - H. Julayhe, Nurnazerah; Rahman, Md Motiar (International Journal of Integrated Engineering, 2021)
Building is the largest consumer of resources and the biggest polluter of the environment, including energy consumption and greenhouse gas emission. Greening existing buildings, an extension of green building concept to existing buildings, can potentially help to improve such issues. Greening process can considerably reduce energy consumption in buildings and thereby reduce the carbon dioxide emission. On the basis of a recent study on energy consumption in residential buildings in Brunei Darussalam, this paper demonstrates the potential savings in energy consumption and reduction of energy cost, if modern and energy-efficient electrical appliances are used in place of the existing conventional features/appliances. The results show that an average household can potentially reduce its yearly energy consumption by 32.74% and they can save annual energy cost of up to 52.20%. It is also seen that the appliances with higher energy consumption, like air conditioners and refrigerators, can offer higher savings of both energy consumption and energy cost, with relatively smaller extra initial replacement costs. A favourable awareness programme by appropriate authority is likely to motivate people to use such practices and help to reduce energy consumption and emission of greenhouse gases.